Treatment of Recurrent Temporomandibular Joint Dislocation - Kahveci, Ramazan (Springer India, 2012)
Temporomandibular joint dislocation is defined as the movement of condyle out of the fossa and the advancement of the posterior surface of the condyle in front of the articular eminence. If this condition becomes chronic, surgical treatment is the only option. The goal of surgical treatment is to reposition the condyle and prevent further recurrences. In this study, a retrospective analysis is presented examining 73 patients and 83 joints that were treated with hook-shaped miniplates and miniscrews fixed to otolog bone grafts. Records were obtained from archives of the Uludag University Medical Faculty, Plastic, Reconstructive and Aesthetic Surgery Department. The duration of postoperative follow-up was 3–30 months. In one case, the miniplate was fractured, and in two cases, abscesses existed. This study aims to emphasize that using miniplates and otolog bone grafts is more cost effective.